TVET Capacity Development in Afghanistan: Introducing Self-Reliant Internship in In-Service Technical Teacher Training at the Technical Teacher Training Institute (TTTI) - Klee, Daniel; Andar, Andar (INVOTEC, 2015)
This paper describes the approach applied to the introduction of self-reliant internship into the in-service TVET (Technical Vocational Education and Training) teacher training at the Technical Teacher Training Institute (TTTI) in Afghanistan. As data show  in 2014, Afghan TVET teachers neither meet the legal requirements set by the government (Bachelor degree) nor have contacts to or work experiences in private or public sector companies. They have no knowledge of the working requirements they are preparing their students for. Consequently, in-service teacher training at the TTTI has to provide it’s learners with knowledge and skills in accordance with the market requirements. Thus, at the TTTI Capacity Building is focusing among others on the multifaceted interdependent relationship between teacher-student-company in order to empower teachers to be able to contribute to the employability of their students. In this respect TTTI’s in-service teacher training foresees the teacher’s participation in a private or public sector self-reliant internship to benefit from the expertise of companies’ work force and employers and actualize their understanding for the world of work. Afghan TVET teachers completing successful the TTTI in-service training are able to train many cohorts of students for the labor market or self-employment with the gained competences. Two subsequent cohorts of TTTI trainees - government employed TVET teachers undergoing in-service teacher training - have been participating for their first time in self-reliant internship in 2013 and 2014. According to the findings, recommendations are given for using the approach of introducing internship in in-service training for TVET teacher capacity building.